2012
DOI: 10.1016/j.injr.2012.04.002
|View full text |Cite
|
Sign up to set email alerts
|

ESR or CRP, which inflammatory measure can accurately replace clinical measures in rheumatoid arthritis?

Abstract: Background: ESR and CRP are two commonly used laboratory inflammatory parameters. The controversy remains which of the two is a better measure to use and which parameter closely reflects the clinical measures of inflammation as well the disease process in Rheumatoid arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
(10 reference statements)
1
6
0
Order By: Relevance
“…ESR is a dependent variable of these factors. The associations among ESR, CRP and DAS28‐CRP(3) are in line with our previous study findings, which demonstrated better overlapping of CRP with clinical features of RA than ESR . DAS28‐CRP(3) showed strong correlation with joint counts, general health measures and pain scale than with CRP, ESR and NLR.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…ESR is a dependent variable of these factors. The associations among ESR, CRP and DAS28‐CRP(3) are in line with our previous study findings, which demonstrated better overlapping of CRP with clinical features of RA than ESR . DAS28‐CRP(3) showed strong correlation with joint counts, general health measures and pain scale than with CRP, ESR and NLR.…”
Section: Discussionsupporting
confidence: 91%
“…The associations among ESR, CRP and DAS28-CRP(3) are in line with our previous study findings, which demonstrated better overlapping of CRP with clinical features of RA than ESR. 16 DAS28-CRP(3) showed strong correlation with joint counts, general health measures and pain scale than with CRP, ESR and NLR. In contrast, NLR correlated better with CRP, ESR, DAS28-CRP(3) and health outcome measures.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…While the question of which inflammatory parameter, ESR or CRP, to use in defining remission has temporarily been put to rest by the recent recommendation of ACR/EULAR 2011 by choosing CRP over ESR, the confusion is still present. As noted in our study CRP represents more closely clinical measures of inflammation . The differences in choice of inflammatory parameter (ESR vs .…”
Section: Discussionmentioning
confidence: 59%
“…The ESR may be aff ected by multiple factors, such as age, anaemia and immunoglobulin concentration. The CRP may be more specifi c for infl ammation, but elevation may relate to smoking and associated insulin resistance 11. RF is an antibody to immunoglobulin G, seen in 80-90% of patients with established RA.…”
mentioning
confidence: 99%